2018
DOI: 10.5120/ijca2018917191
|View full text |Cite
|
Sign up to set email alerts
|

Introducing an Image Processing Method for Evaluation of Clean and Jerk Style in Weightlifting using Measured Biomechanical Parameters

Abstract: Weightlifting is one of the high-medal sports in the Olympic Games. Although one of the most critical weaknesses of this sport is the lack of using new method of technology to improve the quality of player's performance and also decline the referee mistakes. The aim of this paper is to use Image processing to figure out the clinical parameters to examine and measuring the angular kinematic and kinetic features of clean and jerk style in weightlifting. And using this approach for defining the standard pattern f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[6][7][8][9] Angular kinematic features in weightlifting were also investigated by image processing method. 10 Rossi et al 11 simultaneously analyzed both ends of the barbell during weightlifting competitions and concluded that no significant differences were found for any kinematic parameters between right and left sides of the barbell during the snatch and clean. Sato et al 12 examined and validated a commercially available accelerometer which could be easily attached to barbell to get barbell's real-time acceleration, in comparison with kinematic data derived from video records of the barbell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Angular kinematic features in weightlifting were also investigated by image processing method. 10 Rossi et al 11 simultaneously analyzed both ends of the barbell during weightlifting competitions and concluded that no significant differences were found for any kinematic parameters between right and left sides of the barbell during the snatch and clean. Sato et al 12 examined and validated a commercially available accelerometer which could be easily attached to barbell to get barbell's real-time acceleration, in comparison with kinematic data derived from video records of the barbell.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain barbell's trajectory during the snatch, barbell's movement was captured on video by a high‐quality camera, in which the barbell was tracked by applying image processing technology such as pattern recognition 6‐9 . Angular kinematic features in weightlifting were also investigated by image processing method 10 . Rossi et al 11 simultaneously analyzed both ends of the barbell during weightlifting competitions and concluded that no significant differences were found for any kinematic parameters between right and left sides of the barbell during the snatch and clean.…”
Section: Introductionmentioning
confidence: 99%